Teaching Gender in a Transnational Perspective – Challenges, Resistances and Strategies - Christiansen, Connie Carøe; Madsen, Diana Højlund (Kvinder, Køn & Forskning, 2017)
This opening article argues for the need for adopting a transnational perspective in the teaching of gender in the classroom, an approach which has considerable resemblance with Mohanty’s ‘Feminist solidarity or comparative feminist studies model’ of teaching. The article contributes to an on-going scholarly debate on the teaching of gender in higher education by specifying how the transnational feminist perspective could be adopted in practice, both in classrooms and in cooperation between universities. Three points that this perspective gives rise to – the translations of gender, the inherent teaching strategies, and the teaching pedagogy involved – are discussed as they call for reflections on the power dynamics between researchers from the Global North and South and the representations of these poles in class-rooms. The article concludes with some more concrete suggestions for addressing, rather than silencing, the transnational dimension embedded in the practice of teaching gender.